KONDISI GEOLOGI DAN GEOMORFOLOGI KAITANNYA DENGAN DEGRADASI LINGKUNGAN DI KOTA SEMARANG - - Soedarsono (Universitas Islam Sultan Agung, 1970)
Situation of Geography of Town Semarang in corridor of development of Central Java represent the nodes four gateway, that is north corridor where position of geography of Town Semarang as provincial capital of Central Java located in north coast of jawa, south corridor of up at dynamic town like Regency Magelang, Surakarta recognized with corridor Merapi - Merbabu, east corridor up at Regency Demak / Grobogan and west to the Regency Kendal. Town Semarang is one among metropolis in Indonesia and become the provincial capital Central Java. Wide of prefecture 373,7 km², consisted by 16 sub district and 117 chief of village, having strategic geographical position as governance center. Geology condition in Town Semarang lapped over by formation stratigrafi: Alluvium (Qa), Rock of Fire of Gajah Mungkur ( Qhg), Volcano Rock Multiply The Gesik (Qpk), Bullion Formation (Qpj), Resin Formation (Qtd), Frangible Times; Rill Formation (Qpkg), Formation Kalibening (Tmkl), Formation Kerek ( Tmk ) Geology Structure of Semarang city generally in the form of fault, anticline, and breaking. Consisted by the existing Fault type of normal fault, fault shift and fault go up. While for the type of existing anticline cover the Structure of Anticline Bergota, Anticline Candi, and Anticline Karanganyargunung. and for the structure of breaking which is there inTown Semarang that is Breaking of Tinjomoyo I, II And Breaking Jomblang-Jangli Pursuant to process of geomorphology and material of compiler of divisible geomorphology Town Semarang for four set of geomorphology that is set of geomorphology of floods plain, river / fan the aluvial, coastal plain / delta and set of geomorphology of fold mountain. Process the geomorphology that happened [in] Town Semarang [is] decay process, erosion, slide, deposisi material, flooding, precipitation and abrasi. Effect of process the sedimentation that happened at coastal plain aluvial between year 1840 until year 1991 there is coastline growth of equal to 303 meterSeveral things of related to environmental degradasi in Town Semarang for example ground water potency, diffusion reduction irrigate the, ground water intake, changing of ground water condition, landsubsidence, ground, critical farm erosion, erosivitas rain ( R), erodibilitas land;ground ( K), farm erosion Keyword : Geology, Geomorphologyi, Environmental Degradation